Pengaruh Capital Intensity, Umur Perusahaan, dan Sales Growth Terhadap Agresivitas Pajak - Putria, Ditha; Irawati, Wiwit (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the effect of capital intensity, firm age, and Sales Growth on tax aggressiveness. The research was conducted by analyzing the financial statements of companies in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange (IDX) during the period of 2019 to 2023. The population consisted of 129 companies, while the final sample included 175 data points derived from 35 selected companies, using purposive sampling as the sampling technique. The data analysis methods used in this study include descriptive statistics and panel data regression analysis, conducted with the help of EViews 12 Student Version Lite software. The variables involved in this research are: Capital Intensity (X1) as the first independent variable, Firm Age (X2) as the second independent variable, Sales Growth (X3) as the third independent variable, and Tax Aggressiveness (Y) as the dependent variable. The results indicate that the Fixed Effect Model (FEM) was identified as the most appropriate model. Simultaneously, Capital Intensity, Firm Age, and Sales Growth have a significant effect on Tax Aggressiveness. However, the partial test results show that Capital Intensity does not have a significant effect, while Firm Age and Sales Growth each have a significant influence on Tax Aggressiveness.